Пристрій для оцінювання напружено-деформованого стану компоновок низу бурильної колони - Юрич, А. Р. (НТУ "ХПІ", 2014)
В статті пропонується підхід до оцінки напружено-деформованого стану компоновок низу бурильної колони в процесі буріння, за допомогою спеціального пристрою та коригування їх параметрів.

This article offered an opportunity to improve designs of SCE bottom borehole by new scientific and practical decisions aimed at clarifying the conditions of their work in well with industrial data, measured in the hollows using a specially designed device
Tool for definition of intense-deformed state of bottom assembly
Keywords: буріння свердловин; бурильна колона; компоновка низу; профіль стовбура свердловини; drilling; bottom hole assembly; borehole profile